PERGURUAN TINGGI DAN TRANSFORMASI NILAI-NILAI ISLAM DALAM KONTEKS SOSIAL-BUDAYA MASYARAKAT INDONESIA - Samsi Pomalingo (SCAD Independent, 2014)
This article tries to exploration the role of college in values to transforms of Islamic in life of Indonesia pluralistic society. Immeasurable of problems that happened in this nation make proper to get attention of college as independent institute and far from importance of momentary politics. This article also try to give way out how ought to the problem of and difference of diversity have to be accepted as by something there is. For example problem of diversity of culture, social and religion which recently exactly religion values reduce this is humanist and is godlike. Therefore, College has to be optimal of role as realization of responsibility it’s social to nation and society. Social Harmonies represent the infrastructure society to make that is pluralism more having a meaning for the sake of present day and future. There is a thing which is gristle in relationship of pluralities society besides problem of socio-cultural, political and economic. Among others is society relationship and religions in context have theology.